An Efficient Construction of CF3‐Substituted Spirooxindole‐Fused Benzo[a]quinolizidines by a Three‐Component Cyclization. Issue 30 (16th August 2021) - Hu, Yijie; Ye, Liufeiyang; Chen, Jie; Zhang, Hui; Deng, Hongmei; Lin, Jin‐Hong; Cao, Weiguo
Abstract: Benzo[a]quinolizidine is a key subunit in numerous natural products and pharmaceuticals, and therefore its synthesis has received much attention in resent years. Described herein is a convenient three‐component cyclization for the efficient construction of CF3 ‐substituted spirooxindole‐fused benzo[a]quinolizidines by using CF3 ‐propiolate as a building block. This attractive protocol may find great synthetic utility since CF3 ‐containing complex structures were installed by a one‐step cyclization under mild conditions. Abstract : Herein a three‐component cyclization for the efficient construction of CF3 ‐substituted spirooxindole‐fused benzo[a]quinolizidines by using CF3 ‐propiolate as a building block is described. Mild conditions and convenient operations make this protocol attractive.